The Functions of Urban Place Names in the Social Satires by Czeslaw Jankowski - Geben, Kinga (Slavistica Vilnensis, 2018)
[full article, abstract in Polish; abstract in Lithuanian and English] The aim of this article is to research the functions of urban place names which are used in social satires titled, Strolling along in Vilnius (1924–1927), by Czeslaw Jankowski (1857–1929), a famous Polish poet and essayist. The material of the research are social satires which render 150 names of streets, squares, residential areas, buildings and other objects found in the city of Vilnius. Descriptive and interpretive methods have been used in the article. Urban place names are analysed while focusing on (1) place (referential), (2) identifying (characterizing), (3) metaphorical, (4) allusive and (5) organisational (stylistic) functions. Place names used in publicist writing permit to localise the events described and to decipher the author’s attitude to the objects described. The reader can restore the author’s worldview, understand metaphors and allusions created with the help of place names, and assess the use of place names conditioned by the peculiarities of the genre.